Using Movie to Increase Students’ Vocabulary in Politeknik Harapan Bersama - Syaefani Arif R; M. Taufik Qurohman (Universitas Muhammadiyah Mataram, 2018)
This research aims to describe the implementation of Movie for Mechanical Engineering students of Politeknik Harapan Bersama Tegal. The method used is class action research using 2 cycles. The subject of this study is class 6C with 26 people. The student's improvement in vocabulary understanding is 60% in the first cycle. However, the results were categorized as failed because only 10 students received a minimum score of 73 or above 73. So the second cycle is implemented. In the second cycle there is an increase in the percentage understanding vocabulary 75% of the average value of 69-86. So it can be concluded that the student's understanding increases using movie.